Influence of preemergently applied herbicides on the yield and quality of caraway achenes (Carum carvi L.) - Antonín Vaculík (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
Caraway has very low competitive ability against most of weed species. Therefore, it is important to choose a suitable herbicide control, especially at biennial caraway. The experiments with the herbicides applied in caraway were found in pure growth, with variety Kepron (with standard length of vegetative period). The aim of the trials was to find out the differences at achenes yiled and essential oil content after the treatment by the various herbicides, applied preemergently. Also, the selective activity of individual herbicides was tested, including the different doses. The herbicides used in the experiments had enough level of selektivity on the plants of caraway. They had a positive effect on the yiled comparing to non-treated control variant in all observed years. There was no statistically significant difference in essential oil kontent between the treated variants and non-treated control. On the basis of these results, the most suitable herbicide was chosen for the „minor“ registration for caraway.